1993
DOI: 10.1159/000126515
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression of KA Type and NMDA Receptors and of a Glycine Transporter in the Rat Pineal Gland

Abstract: This study, using in situ hybridization histochemistry, revealed the pineal gland strongly expressed mRNAs of kainic acid-type receptors, N-methyl-D-aspartate receptors and the glycine transporter. These findings demonstrated the presence of dense glutamatergic innervation of the pineal gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 17 publications
1
8
1
1
Order By: Relevance
“…This contrasts with the total lack of AMPA-type receptor expression reported in the pineal gland of the rat [7], However, low levels of subunit expres sion in individual cells of small size, like sparsely distrib uted glial cells, may have not been detected by the situ hybridization histochemistry in this species. In the pri mate pineal gland, the unique presence of GluRl charac terizes glial cells in the distal part while GluR4 character izes glial cells mainly located in the proximal part as well as astrocytic processes within the distal part.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…This contrasts with the total lack of AMPA-type receptor expression reported in the pineal gland of the rat [7], However, low levels of subunit expres sion in individual cells of small size, like sparsely distrib uted glial cells, may have not been detected by the situ hybridization histochemistry in this species. In the pri mate pineal gland, the unique presence of GluRl charac terizes glial cells in the distal part while GluR4 character izes glial cells mainly located in the proximal part as well as astrocytic processes within the distal part.…”
Section: Discussioncontrasting
confidence: 75%
“…The absence of expression of AMPA-type receptor sub unit reported in the pineal gland of the rat by in situ hybridization suggests that the lack of AMPA-type recep tors in pinealocytes is a common trait in mammals [7], However, AMPA-sensitive glutamate binding sites have been described in the rat pineal gland [5]. This discrepan cy between data obtained in the rat may be related to low levels of AM PA receptor subunit expression that have not been detected using oligonucleotidic probes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The class I mGluR5 receptor is also present in pineal cells and triggers Ca 2ϩ efflux from intracellular stores Pabst and Redecker, 1999). Other ionotropic Glu receptors have also been reported in the pineal glands of several species (Sato et al, 1993;Mick, 1995;Yatsushiro et al, 2000). In the rat pineal gland GluR1 is functionally expressed in pinealocytes and may participate in a Ca 2ϩ -signaling cascade that enhances and expands the Gluergic signal throughout the pineal gland (Yatsushiro et al, 2000).…”
Section: B Other Nonadrenergic Nonpeptidergic Transmitters Of the Pmentioning
confidence: 99%
“…On stimulation of the receptor, Ca 2+ was released from internal stores, possibly from the endoplasmic reticulum, resulting in a transient increase of intracellular [Ca 2+ ] (Yatsushiro et al, 1999). In the case of ionotropic receptors, the presence of mRNAs and of some of the subunit proteins of three classes of receptor, i.e., NMDA‐, kainate‐, and α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid (AMPA)‐type receptors, has been shown in pineal glands (Sato et al, 1993; Toole et al, 1993; Wisden and Seeburg, 1993; Petralia et al, 1994; Mick, 1995; Moller et al, 1995). Very recently it was found that only the AMPA‐type glutamate receptor type 1 subunit was functionally expressed in pinealocytes (Yatsushiro et al, 2000).…”
mentioning
confidence: 99%